2024
DOI: 10.3390/v16020239
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Drug Resistance Detected by Next-Generation Sequencing among ART-Naïve Individuals: A Systematic Review and Meta-Analysis

Fei Ouyang,
Defu Yuan,
Wenjing Zhai
et al.

Abstract: Background: There are an increasing number of articles focused on the prevalence and clinical impact of pretreatment HIV drug resistance (PDR) detected by Sanger sequencing (SGS). PDR may contribute to the increased likelihood of virologic failure and the emergence of new resistance mutations. As SGS is gradually replaced by next-generation sequencing (NGS), it is necessary to assess the levels of PDR using NGS in ART-naïve patients systematically. NGS can detect the viral variants (low-abundance drug-resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Quality assessment and standardization of NGS methodologies are urgently needed to facilitate data comparison between studies ( 11 , 15 ). There is also a need to define the optimal threshold for LA-RAMs for clinical applications ( 11 , 13 , 14 , 16 , 17 ). Several studies have reported that LA-RAMs detected at levels of 2–9% were linked to virologic failure ( 15 , 18 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality assessment and standardization of NGS methodologies are urgently needed to facilitate data comparison between studies ( 11 , 15 ). There is also a need to define the optimal threshold for LA-RAMs for clinical applications ( 11 , 13 , 14 , 16 , 17 ). Several studies have reported that LA-RAMs detected at levels of 2–9% were linked to virologic failure ( 15 , 18 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, due to limited sample volumes, we were not able to perform repeat/duplicate testing to evaluate the reproducibility of detection of mutations by NGS. Other approaches, such as the use of unique molecular identifiers during reverse transcription, could be used to assess the frequency of PCR- and sequencing-based errors in NGS data ( 13 , 17 , 26 , 27 ). Finally, parameters required for clinical assay validation were not evaluated in this study since the AB kit is not cleared by the U.S. FDA for clinical use.…”
Section: Discussionmentioning
confidence: 99%